2022
DOI: 10.1097/jfn.0000000000000402
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Use and Case Characteristics of Commercial Sexual Exploitation of Children

Abstract: Introduction The overall goal of this study was to provide further information about the characteristics of commercial sexual exploitation of children (CSEC) victims by comparing the characteristics of a known victim pool to high-risk patients identified. The specific objectives of this study were to describe patient demographic characteristics, pediatric healthcare use, familial psychosocial characteristics, and child sexual abuse case characteristics present in youth identified as high risk for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The lack of education was attributed to family poverty, limited economic opportunities in the community, or the distance to schools. While in other studies, mainly conducted in the United States, youth did have access to education, but problems such as dropping out of school, lack of education about sexual exploitation, and low grades were associated with sexual exploitation (Adjei & Saewyc, 2017;Chohaney, 2016;Greeson et al, 2019a;Hurst, 2021;Hornor et al, 2022;Servin et al, 2015).…”
Section: Study Characteristicsmentioning
confidence: 94%
See 3 more Smart Citations
“…The lack of education was attributed to family poverty, limited economic opportunities in the community, or the distance to schools. While in other studies, mainly conducted in the United States, youth did have access to education, but problems such as dropping out of school, lack of education about sexual exploitation, and low grades were associated with sexual exploitation (Adjei & Saewyc, 2017;Chohaney, 2016;Greeson et al, 2019a;Hurst, 2021;Hornor et al, 2022;Servin et al, 2015).…”
Section: Study Characteristicsmentioning
confidence: 94%
“…Multiple studies (n = 17), from several continents, found a connection between compromised parenting and family functioning and sexual exploitation (the United States, Canada, Mexico, Brazil, the United Kingdom, Uganda, and the Philippines). This risk factor was captured in these studies via different measures (e.g., poor nurturing, conflicts between child and parents, unhealthy family relationships, parental attachment, and caregiver absence) and was found in both male and female youth (Acharya & Bryson Clark, 2021;Alderson et al, 2021;Chohaney, 2016;Cole, 2018;Fraley & Aronowitz, 2021;Helpingstine et al, 2021;Homma et al, 2012;Hornor et al, 2022;Louie, 2018;Macias-Konstantopoulos et al, 2013McNeal & Walker, 2016;O'Brien, 2018;Reid & Piquero, 2016;Self-Brown et al, 2021;Silverman et al, 2007;Williams et al, 2012). Three studies made a gender comparison, of which two found gender differences.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…exploitation (T/E) may seek health care in a variety of settings, [1][2][3] making it essential that pediatric providers anywhere are equipped to recognize potential T/E and respond appropriately. The guidance offered here is aimed to assist health care professionals in recognizing previously unidentified T/E, as well as in providing a basic initial response to suspected and confirmed cases of exploitation.…”
mentioning
confidence: 99%